2021
DOI: 10.17513/spno.30879
|View full text |Cite
|
Sign up to set email alerts
|

Biobanking of Patient-Derived Xenografts as a Basis for Translation Research in Oncology

Abstract: Высокой уровень заболеваемости и смертности от злокачественных новообразований делает разработку новых терапевтических препаратов актуальной задачей современной медицины. Чтобы потенциал научных открытий мог быть реализован в клинической практике, важным условием является доступ к биологическим образцам и их сопроводительным данным для тщательной оценки потенциальной терапевтической мишени, ее связи с конкретным заболеванием и выраженностью противоопухолевого ответа при воздействии изучаемым препаратом. Развит… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…obtained from patients with colorectal cancer, BC and other types of malignancies have also demonstrated that tumoroids can be used as a test system to predict clinical response to chemotherapy (Danilova et al, 2021;Yao et al, 2022). A number of researchers question the feasibility of PDX in personalized medicine, particularly for selecting targeted therapy or monitoring tumor response to therapy, as PDX is relatively labour-intensive and time-consuming (Sachs et al, 2018), but PDX biobanks are created and successfully used (Abdirahman, 2020;Kiblitskaya, Shevchenko, Pandova, and Ardzha, 2021).…”
Section: Bioresource Collectionsmentioning
confidence: 99%
“…obtained from patients with colorectal cancer, BC and other types of malignancies have also demonstrated that tumoroids can be used as a test system to predict clinical response to chemotherapy (Danilova et al, 2021;Yao et al, 2022). A number of researchers question the feasibility of PDX in personalized medicine, particularly for selecting targeted therapy or monitoring tumor response to therapy, as PDX is relatively labour-intensive and time-consuming (Sachs et al, 2018), but PDX biobanks are created and successfully used (Abdirahman, 2020;Kiblitskaya, Shevchenko, Pandova, and Ardzha, 2021).…”
Section: Bioresource Collectionsmentioning
confidence: 99%